2021
DOI: 10.1108/mip-01-2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

Awe, consumer conformity and social connectedness

Abstract: PurposeThe purpose of this paper is to explore the effect of the feeling awe on individuals' endorsement of conformist attitudes in consumption choices and the mediating role of social connectedness in generating this effect.Design/methodology/approachWe test our hypotheses across three studies. Study 1 used an online survey. Study 2 and 3 conducted two laboratory experiments to induce awe and measured consumer conformity in two consumption choice tasks.FindingsThis research shows that both dispositional awe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…For example, social connectedness stands out as one potential mediator. Awe increases global interconnectedness, including social connectedness with others (Piff et al, 2015; Shiota et al, 2007; Yang et al, 2021). Social connectedness in turn may foster GSC by strengthening the social fabric that connects the self at different temporal points, incorporating others into one’s self-concept, and seeing oneself the way others used to do so (Sedikides et al, 2016; van Tilburg et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, social connectedness stands out as one potential mediator. Awe increases global interconnectedness, including social connectedness with others (Piff et al, 2015; Shiota et al, 2007; Yang et al, 2021). Social connectedness in turn may foster GSC by strengthening the social fabric that connects the self at different temporal points, incorporating others into one’s self-concept, and seeing oneself the way others used to do so (Sedikides et al, 2016; van Tilburg et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Awe as an emotional theme that continues to be valued [ 19 , 22 , 23 ] has been shown that marketers can conduct sales activities by eliciting awe [ 60 ], and valuing its valuable role in the marketing field can provide support to the business and marketer side, providing theoretical support for practical marketing programs [ 23 , 61 ]. The research on the motivational effects of anxiety in marketing is mixed; on the one hand, anxiety may cause consumers to develop avoidance behavior, making them want to move away from the stimulus that induces anxiety [ 29 ]; on the other hand, anxiety may also cause consumers to develop an approach behavior that leads to certain actions [ 27 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…According to SDT, the self-reflective conditions that transformative tourism experiences create for tourists through environmental stimuli help them develop a more open worldview [25,26], which can enhance the dispositional awe of individuals [56]. Meanwhile, dispositional awe helps to improve the individual's social connectedness [57]. Ultimately, tourists' prosocial behaviors are reinforced lastingly and effectively by the combined effect of three major motivations: emotion, drive, and intrinsic need.…”
Section: Overview Of Key Findingsmentioning
confidence: 99%